Effect of Methotrexate on the Liver Enzymes and Lipid Profile in Adult Female Albino Mice (Baghdad Science Journal, 2013)
Methotrexate (MTX) was used for treatment of malignancies and now is widely used in treatment of rheumatoid arthritis. In this research the evaluation of the effects of MTX on some liver enzymes and lipid profile was studied. Twenty four adult female mice divided into three groups (8 mice each). The first two groups were treated with MTX while the third group was used as a control. MTX was intraperitoneally given at 50 µg/ml and 75 µg/ml to the first and second groups respectively for 35 days ,whereas the control group was intraperitoneally injected with normal saline. The results showed a significant (p